A case report of inflammatory fibrosis in the mandible, probably caused by traumatic lesions - SAKAMOTO, Ichiro; ASAHINA, Izumi; ENOMOTO, Shoji; HIGASHINAKAGAWA, Makiko; OKADA, Norihiko; ABE, Masato (Japanese Journal of Oral and Maxillofacial Surgery, 2001)
We report a rare case of fibrosis in the mandible that was probably caused by traumatic lesions. A 36-year-old man was referred to our clinic for evaluation and treatment of a radiolucent lesion in the right mandibular canine region. The mucosa in this region was normal. There was no cortical expansion. Computed tomography revealed a soft tissue mass at the right side of mandible. It measured 25×15×12mm and had poorly defined borders with resorption of the buccal and lingual cortical bones. Biopsy of the lesion showed inflammatory fibrous tissue. Under general anesthesia, the patient underwent extirpation of the lesion. Histopathologically, fibrous tissue consisting of interlacing collagenous fibers was noted. The course was uneventful, and bone regeneration in the bone cavity was revealed by computed tomography 1 year after surgical treatment.